Quantitative Analysis about simulation and gaming in the oral production in English - Laura Angelini; Amparo García-Carbonell; Nieves Martínez Alzamora (Universitat Politècnica de València, 2015)
The present work seeks to provide methodological innovation in the teaching English as a foreign language and promote an  accurate  development  of  oral  abilities. This   article   focuses   on   a   quantitative research about the development the oral production  in  English  by  means  of  the simulation    and    gaming    methodology. The  objective  of  this  research  is  two-fold: first,  to  verify  if  a  telematic  simulation proves  the  standards  of  an  efficient  tool to  develop  the  oral  production  in  English, and second, to delve into research from in-classroom practice of English. Three studies are   conducted,   namely,   a   comparative analysis of the global assessment of the variable oral expression pre and post treatment in the experimental groups E1 and E2, a comparative study pre and post treatment  of  the  sub-variables  delivery, content, organization and language related to  the  oral  production,  and  a  study  of concordance between three external examiners.     Results     prove     significant progress  in  the  variable  oral  production post-treatment,  and  in  the  sub-variables content   and   organization;   a   moderate progress in the sub-variables delivery and language use in the experimental groups.